Decision-making in the public management and the use of the evaluation:: Analysis of three municipalities of the metropolitan region of Natal - Cláudio Roberto de Jesus; Lindijane de Souza Bento Almeida; Glenda Dantas Ferreira (Revista Aval, 2019)